Comparative morphology and taxonomy of the Wrangelieae, Sphondylothamnieae, and Spermothamnieae (Ceramiaceae, Rhodophyta). - Gordon, Elizabeth A. (Editorial and Publications Section, CSIRO, 1972)
Australian Journal of Botany Supplementary series; Suplement number 4